Swim Training Reduces Metformin Levels in Fructose-Induced Insulin Resistant Rats - Kuei-Yu Chien; Chi-Chang Huang; Ku-Fu Hsu; Chia-Hua Kuo; Mei-Chich Hsu (Frontiers Media S.A., 2011)
Purpose: Regular exercise training and metformin medication are widely considered to increase insulin sensitivity and protect against type 2 diabetes, however, evaluating the effect of exercise training on the disposition and pharmacokinetics of metformin is unclear. Methods: We investigated the effect of a 4-wk swim training program (45 min/day, 5 days/wk) on the pharmacokinetics for the use of metformin in fructose-induced insulin resistant rats. Fructose-induced insulin resistant rats were assigned into two groups (n=6/group): swim training with metformin (SM), and non-swim training with metformin (CM). Blood samples were collected from 12 h-fasted rats at baseline and at 0.25, 0.5, 0.75, 1, 2, 3, 4, 6, 8, 10, and 12 h after an oral glucose tolerance test (OGTT) with administration of a single dose of metformin (450 mg/kg). Results: Our study revealed that both glucose and insulin levels in the SM group were significantly lower than those in the CM group at 15 min following OGTT. The maximum concentration (Cmax) and area under the serum concentration-time curve (AUC) for the SM group were significantly lower than CM group. The apparent distribution volume (Vd) and the time-averaged total body clearance (CL) for the SM group were significantly higher than those for the CM group. There were no significant differences in the time to maximum concentration (Tmax) or the time to half-life concentration (t1/2) between the two groups. Conclusions: Our data demonstrate that swim training reduces metformin serum levels. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.